A study of the normative and jurisprudential modifications of the crime of omission of family assistance - Gómez Vargas, Ángel (2021)
The crime of omission of family assistance was incorporated into our legal system through Law No. 13906, enacted on March 24, 1962. It has been subject to multiple legal and juridical modifications; moreover, since 2015, it has increased excessively, so that it constitutes more than half of the total number of judicial processes at the national level. Due to its importance, this article, from a practical approach, analyzes its normative and jurisprudential modifications so that this crime can be more easily understood.